2016
DOI: 10.1002/stem.2296
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: When Colonies Are Not Clones: Evidence and Implications of Intracolony Heterogeneity in Mesenchymal Stem Cells

Abstract: The emergence of heterogeneity in putative mesenchymal stem cell (MSC) populations during in vitro expansion is not appreciated fully by the various communities who study, engineer, and use such stem cells. However, this functional diversity holds direct implications for basic research and therapeutic applications of MSCs that require predictable phenotypic function and efficacy. Despite numerous clinical trials pursuing MSC therapies, the in vitro expansion of homogeneous populations to therapeutically releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 37 publications
2
69
0
Order By: Relevance
“…Continuous labeling between days 0–9 showed that matrix protein accumulation by MSCs lagged behind that of chondrocytes, and differed in its spatial organization. Notably, there was high MSC-to-MSC variation in the labeled extracellular protein present (Figs 6a,c and S8a,b), consistent with the heterogeneous nature of this cell population222324. This heterogeneity manifested in two ways: in the intensity of the labeled matrix proteins and in the pattern of matrix protein distribution.…”
Section: Resultssupporting
confidence: 68%
“…Continuous labeling between days 0–9 showed that matrix protein accumulation by MSCs lagged behind that of chondrocytes, and differed in its spatial organization. Notably, there was high MSC-to-MSC variation in the labeled extracellular protein present (Figs 6a,c and S8a,b), consistent with the heterogeneous nature of this cell population222324. This heterogeneity manifested in two ways: in the intensity of the labeled matrix proteins and in the pattern of matrix protein distribution.…”
Section: Resultssupporting
confidence: 68%
“…Improvements on single-cell morphological analysis using high-dimensional singlecell classification techniques such as SPADE or viSNE could allow for identification of morphologically distinct subpopulations of MSCs that could be enriched for immunotherapies (52). These approaches could also provide insight into the progression and establishment of MSC heterogeneity as it relates to differences in donor (or tissue) source and in manufacturing (40,53). Advancements in live-cell tracking and monitoring in vitro would further allow for direct correlation of early morphological phenotypes with assay outcomes (15,54).…”
Section: Morphological Features Of Mscs After Ifn-γ Stimulation Corrementioning
confidence: 99%
“…In fact, these challenges and benefits from addressing emergent population heterogeneity are not limited to MSCs, and they can be considered for other tissue-derived stem cells and induced pluripotent cell populations and can be overcome by sorting by label-free biophysical markers or by biophysical or other characteristics. 47 Because of the extremely low yields of BMSC progenitors (typically 0.001%–0.01%) obtained from bone marrow aspirates, large quantities of bone marrow must be procured, which can cause additional donor site morbidity. 48 In addition, several passages are required in order to separate the hematopoietic population and other cell types from the pure BMSCs.…”
Section: Stem Cells In Bone Regenerationmentioning
confidence: 99%